Effects of Mo Layer on the High-Temperature Oxidation Resistance Mechanism of Micro-Melted NiCr Coating on Zirconium Alloys Surface - LIU Gengming, SONG Guoqing, XUE Kanghui, CHEN Yong (Cailiao Baohu)
In order to enhance the high-temperature oxidation resistance of Zr alloy cladding surface coatings, a composite technique combining multi-arc ion plating and laser melting(LMM) was employed to fabricate Mo/NiCr coatings on the surface of Zr alloy cladding. The SEM morphology and elemental distribution of the coatings before and after oxidation were examined. Additionally, the composition of the coatings was determined to evaluate the changes in their high-temperature oxidation resistance. Results showed that the surface porosity of the coatings was reduced following the LMM treatment. The LMM power for the Mo/NiCr coating was greater than that for the NiCr coating, and the surface of the coating exhibited characteristics of nonequilibrium solidification microstructures. With the addition of the Mo coating, the diffusion distance of the Zr alloy after LMM at higher power increased from 4.0 μm to 18.5 μm from the coating surface. After the samples were oxidized for 30 min under conditions of 1 000 ℃ in air and water vapor, the extent of diffusion of the Zr alloy towards the Mo/NiCr coating was significantly lower than that towards the NiCr coating. This was attributed to the presence of the Mo layer, which acted as a diffusion barrier, inhibiting the interdiffusion between NiCr and Zr. Consequently, oxygen had difficulty reacting with Zr through the Mo layer to form Zr2O, thereby preventing the transformation of β-Zr into the brittle α-Zr phase. In the coating, Zr2O served as a diffusion pathway for O, while the brittle α-Zr phase regions were more prone to the formation of Zr2O, leading to an increased number of diffusion channels and significantly weakening the oxidation resistance of the coating. Consequently, among the four tested coatings, the LMM-NiCr coating subjected to steam oxidation exhibited the deepest diffusion of O, reaching a distance of 14.0 μm from the coating surface, whereas the LMM-Mo/NiCr coating under the same conditions showed the shallowest diffusion of O, extending only to 1.5 μm from the coating surface. This indicated that the addition of Mo could enhance the power of LMM, obstructing the diffusion of Zr towards the coating surface during the LMM process, as well as impeding the diffusion of O towards Zr and the diffusion of Zr towards the coating surface during oxidation. This indirectly prevented the emergence of diffusion pathways for O and suppressed the formation of diffusion pores for H2O. The addition of Mo improved the high-temperature oxidation resistance of the coating.